The Charter and Ordinances of the City of Richmond, at 196-197, ch. 34, § 42 (1869) - (:unkn) unknown (General Publisher, 1869)
If any person engaged in military exercise shall fire or discharge, in any street or public alley of this city, any cannon, gun, pistol, or any other firearms, except on the fourth of July, the twenty-second of February and the nineteenth day of October, or at military burial or some extraordinary occasion allowed by the Mayor (and by him notified through the newspaper, or by posting handbills or otherwise), or if any person shall, in any street or public alley in said city, play at bandy or throw snowballs, stones or other missiles, or discharge arrows form a bow or cross-bow, or blow a horn, he shall be fined not less than one nor more than ten dollars.]
--
Keywords: DISCHARGE